2016
DOI: 10.1039/c6ra03193e
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based prediction of CAD response factors of dammarane-type tetracyclic triterpenoid saponins and its application to the analysis of saponin contents in raw and processed Panax notoginseng

Abstract: Structure-based impacts of saponins on CAD response factors are discovered, and in-depth analysis of saponins in Panax notoginseng is implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…20(S)- and 20(R)-Rg 3 are the only pair of C-20 stereoisomers reported in raw P. notoginseng . However, based on our results ( Peng et al, 2016b ), only 20(S)-form stereoisomeric saponins could be found in raw P. notoginseng . Take 20–80 head raw herbs obtained from Yunnan province as an example, 20(S)-notoginsenoside R 1 , 20(S)-Rg 2 and 20(S)-Rh 1 were found, and the amount was in the range of 1.0–1.9, 0.5–1.5, and 0.3–2.1 mg/g, respectively.…”
Section: Chemistrymentioning
confidence: 71%
See 1 more Smart Citation
“…20(S)- and 20(R)-Rg 3 are the only pair of C-20 stereoisomers reported in raw P. notoginseng . However, based on our results ( Peng et al, 2016b ), only 20(S)-form stereoisomeric saponins could be found in raw P. notoginseng . Take 20–80 head raw herbs obtained from Yunnan province as an example, 20(S)-notoginsenoside R 1 , 20(S)-Rg 2 and 20(S)-Rh 1 were found, and the amount was in the range of 1.0–1.9, 0.5–1.5, and 0.3–2.1 mg/g, respectively.…”
Section: Chemistrymentioning
confidence: 71%
“…For ELSD and MS detectors, CH 3 COOH and HCOOH are usually added into mobile phases to assist a better volatilization of saponin analytes ( Chan et al, 2007 ; Sun et al, 2009 ; Bae et al, 2013 ; Wan et al, 2013 ). Our group has developed a HPLC-CAD method to simultaneously separate 22 saponins existed in raw and processed notoginseng, in which 5 pairs of 20(S)- and 20(R)-ginsenoside epimers were separated ( Peng et al, 2016b ). In addition, using an appropriate column with small particle size can gain higher efficiency and better isolation.…”
Section: Chemistrymentioning
confidence: 99%
“…It has the effect of good for body to remove heat and calming liver and reducing blood pressure. Some studies have shown that Sanchi flower not only has a significant effect on lowering blood pressure, but also has a small side effect on regulating immune function, promoting NK cell activity and promoting sleep (Peng et al 2016). On May 13, 2016, the health and Family Planning Commission of Yunnan Province officially approved that Sanchi flower and stem leaf can be managed according to common local characteristic food raw materials, and Sanchi flower and stem leaf officially entered the food industry (Zhang et al 2018).. Superfine grinding has emerged as a novel methodology in recent years in processing and development of functional foods.…”
Section: Introductionmentioning
confidence: 99%
“…Peng et al. [20] developed an HPLC–charged aerosol detector method for the analysis of saponin contents in notoginseng. Among these saponins determined, notoginsenoside R 1 (NG-R 1 ), ginsenoside Rg 1 (G-Rg 1 ), ginsenoside Re (G-Re), ginsenoside Rb 1 (G-Rb 1 ), and ginsenoside Rd (G-Rd) were regarded as the major active constituents [21] .…”
Section: Introductionmentioning
confidence: 99%